Adipokines as predictive factor of cardiac function in pediatric patients with chronic kidney disease - Villasis-Keever, Miguel Angel; Zurita-Cruz, Jessie Nallely; Zepeda-Martinez, Claudia; Alegria-Torres, Gabriela; Serret-Montoya, Juana; Estrada-Loza, Maria de Jesus; Hernández-Hernández, Beatriz Carolina; Alonso-Flores, Sara; Zavala-Serret, Monica (Frontiers in Endocrinology, 2023)
Background: Adipokines are associated with cardiovascular disease; in chronic kidney disease (CKD) patients adipokines could be useful prognostic factors. Objectives. To explore whether leptin and adiponectin in kidney replacement therapy (KRT) children could have a role on their cardiac function, in the long-term. Design: Prospective cohort study was performed with pediatric KRT patients, aged 8 to 17 years who were undergoing hemodialysis or peritoneal dialysis. At enrollment, lipid profile, adipokines (leptin, leptin receptor, free leptin, and adiponectin), anthropometric measurements and cardiological evaluation were determined. At two-year follow-up, a new cardiological evaluation was performed. Statistical analysis: Quantitative data are presented as median and interquartile range (IQR). Mann-Whitney U test and Chi-squared were used for the between-group comparison. Multivariate analyzes were performed to determine the association of adipokines levels with ventricular ejection fraction (LEVF). Results: We included 56 patients, with a median age of 12.5 years. In the first cardiological evaluation, median LVEF was 70.0% (IQR 61%, 76%), 20 patients (35.7%) had some cardiovascular condition, and 10 (17.8%) altered LVEF. At 24-month follow-up, the median LVEF was 70.5% (IQR 65.1%, 77%), while the delta-LVEF values was 3% (IQR -6.5%, 7%). Delta-LVEF were correlated with baseline adipokines serum levels, and the only positive correlation found was with free leptin (r=0.303, p=0.025). In multivariate analysis, levels of free leptin (Coef. 0.12, p<0.036) and leptin (coef. 1.72, p=0.049), as well as baseline LVEF (Coef. -0.65, p<0.001) were associated with delta-LVEF. Conclusions: Free leptin, leptin and LVEF at the beginning of follow-up were associated with the LVEF decrease at the 24-month follow-up in KRT children.